(untitled) - Blanc, Iris; Iris Blanc; Cathy Vento (Boston, Mass.,United Kingdom, 2003)
The Performing Series takes students to a higher level of learning through applied and project-based activities that go beyond the mechanics of the software. Most textbooks begin by teaching students software skills. The Performing Series presents various business documents first, then shows students the Office 2003 skills they need to create them. This approach shows students the relevance of what they are learning as they apply technology to task
Keywords: Microsoft Office; Microsoft Word; Microsoft Access; Microsoft PowerPoint